Insurance Options for Addressing Climate Change - Miller, Alan; Swann, Stacy (International Finance Corporation, Washington, DC, 2018)
Emerging markets are especially vulnerable to threats from climate change. Storms, droughts, and floods jeopardize the livelihoods of farmers, while extreme temperatures limit the ability of workers to be outdoors. Insurance is one tool that can help emerging markets adapt to climate change by heading off threats before they become disasters. Some pilot projects around the world are showing promise in using insurance to help emerging markets reduce the impact of climate change.